Dioctophyme renale: Prevalência e fatores de risco de parasitismo em cães no distrito de São Cristóvão, Três Barras, Santa Catarina, Brasil - Pedrassani, Daniela; Do Nascimento, Adjair Antonio [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (FapUNIFESP (SciELO), 2017)
Dioctophyme renale is a nematode that can be found parasitizing the kidney, peritoneal cavity and, rarely, other organs of canids and mustelids. This disease has high occurrence in the municipality of Três Barras, state of Santa Catarina, thus making this an interesting area to study the epidemiological aspects of infection by D. renale in dogs. Among 197 dogs, 14.2% showed the parasite eggs in urine and 16.4% showed IgG antibodies anti-D. renale in serum samples according to the indirect ELISA method; among seropositive dogs, 15 (37.5%) animals did not show any parasite eggs in their urine. Parasitism was more frequent in females, and there was no finding of interference from age on parasitism. Factors such as water potential and presence of paratenic hosts in the studied region were reported by the owners of dogs and may have contributed to the occurrence of parasitism.
Dioctophyme renale: Prevalence and risk factors of parasitism in dogs of são cristóvão district, três barras county, santa catarina state, brazil
Keywords: Dioctophyme renale; ELISA; Epidemiology; Kidney worm